2000
DOI: 10.1200/jco.2000.18.15.2908
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous T-Cell Lymphoma: Review and Current Concepts

Abstract: MF and SS are the most common forms of CTCL. The etiology of this disease is still unknown. Patients may go for months to years with skin abnormalities before being diagnosed. MF/SS is an indolent disease and patients with T1 disease have a normal life expectancy. Patients who undergo transformation to large-cell lymphoma (8% to 23% of patients) have a poor prognosis, with mean survival ranging from 2 to 19 months. Treatment for MF/SS continues to be palliative. There are many new therapies that are currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
2
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(191 citation statements)
references
References 110 publications
3
183
2
3
Order By: Relevance
“…We have selected these tumors because MF and SS cells are usually CD3 ϩ CD4 ϩ CD45RO ϩ , a phenotype similar to nontransformed activated T cells producing IL-17. 25 We found that Sezary cells express IL-17, a feature associated with infiltration of polymorphonuclear neutrophils into these lesions. The IL-17-induced release of IL-8 may be partly responsible for neutrophil recruitment.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…We have selected these tumors because MF and SS cells are usually CD3 ϩ CD4 ϩ CD45RO ϩ , a phenotype similar to nontransformed activated T cells producing IL-17. 25 We found that Sezary cells express IL-17, a feature associated with infiltration of polymorphonuclear neutrophils into these lesions. The IL-17-induced release of IL-8 may be partly responsible for neutrophil recruitment.…”
mentioning
confidence: 66%
“…However, these results must be cautiously interpreted because IL-17 may also be derived from nontransformed CD4 T cells infiltrating the biopsies and certain MF/SS have also been reported to lose their CD4 expression. 25 In addition, some infiltrating dendritic cells may express CD4.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Transformation of mycosis fungoides offers poor prognosis, with extracutaneous spread and a median survival of less than 2 years. 17,18 In SS, transformation into large cells may also occur at either the blood or skin level. 19 In epidermotropic CTCLs, progression to advanced stage, large cell transformation or leukemic B2 phase can take place within 2 years, defining patients with rapid progressive disease and poor survival.…”
Section: And Gil and Peters 5 )mentioning
confidence: 99%
“…For most patients, deletion ranged from 2.5 to 6 Mb. Six patient samples (11,18,19,20,21 and 25) exhibited very limited deletion (less than 1 Mb) detected by either one BAC clone and/or a few oligonucleotide probes.…”
Section: Cdkn2a-cdkn2b Loss In Cutaneous Lymphomasmentioning
confidence: 99%
“…Approximately two-thirds of these lymphomas are of T-cell origin, and the pathogenesis and management of both T-and B-cell cutaneous lymphomas have been recently reviewed. [1][2][3][4][5][6] The most common form of cutaneous T-cell lymphoma (CTCL) is mycosis fungoides (MF), accounting for around 60% of new cases. Sé zary syndrome (SS) is much rarer and accounts for only 5% of CTCL cases.…”
Section: Introductionmentioning
confidence: 99%